Weld design and fabrication for RHS connections. Issue 1 (6th February 2013) - McFadden, Matthew R.; Packer, Jeffrey A.
Abstract The 2010 AISC Specification for Structural Steel Buildings has expanded its scope in chapter K "Design of HSS and Box Member Connections" to include a section K4 "Welds of Plates and Branches to Rectangular HSS". This paper discusses the historical development of the effective weld properties and analyses the structural reliability of the provisions. Additionally, there is a discussion on recent changes in U.S. and Canadian specifications/ codes with regard to the limit states for fillet weld design and the acceptance/rejection of the (1.00 + 0.50 sin1.5θ) term. Finally, there is a discussion of the details of an experimental research programme being performed at the University of Toronto in collaboration with AISC to determine the weld effective length in RHS T‐connections under branch in‐plane bending moments. In conclusion, it is found that the inclusion of the (1.00 + 0.50 sin1.5θ) term for RHS gapped K‐connections as well as T‐ and X‐connections, based on the limit state of shear failure along the effective throat of the weld, may be unsafe for fillet weld design when used in conjunction with the current effective weld length rules.